New development: Fundraising in UK charities—stepping back from the abyss. Issue 3 (16th April 2017) - Hind, Andrew
Abstract : Fundraising techniques used by charities can enhance or diminish public trust. The dangers of questionable and over-aggressive fundraising practices are very real. In particular, in the UK, the 'Olive Cooke affair' in 2015 triggered a highlevel examination of fairly widespread dubious practices. In this article, the reflections of a key actor on the events surrounding the affair, and subsequent fallout, are examined. It is argued that this whole saga has the potential to encourage the development of a charity sector that is more trusted by the public; a sector that has stepped back from the abyss.